2022
DOI: 10.1007/s11524-022-00611-z
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Urban Living on Suicidality and Self-Harm in the UK and Ireland

Abstract: We conducted a systematic review to answer the following: (a) Is there any evidence to support increased prevalence of suicidality and self-harm (i.e. self-harm or suicidality) in urban versus rural environments? (b) What aspects of the urban environment pose risk for suicidality and self-harm? Thirty-five studies met our criteria. Our findings reflect a mixed picture, but with a tendency for urban living to be associated with an increased risk of suicidality and self-harm over rural living, particularly for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
1
8
1
Order By: Relevance
“…Although our results were consistent with several Canadian studies [16,17,21], research from Ireland and the United Kingdom revealed an inverse association between self-harm and rurality [24,40]. That is, after controlling for deprivation, the risk of self-harm was higher in urban compared with rural areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although our results were consistent with several Canadian studies [16,17,21], research from Ireland and the United Kingdom revealed an inverse association between self-harm and rurality [24,40]. That is, after controlling for deprivation, the risk of self-harm was higher in urban compared with rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…The rural-urban pattern in Canada is different than in the United Kingdom and Ireland, where rates of self-harm and suicide tend to be higher in urban areas after adjusting for socio-economic deprivation [24]. In Canada, there is a pronounced gradient in rates of self-harm and suicide across levels of deprivation [25,26], though how this influences rural-urban differences is less clear.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Attention can be ultimately directed towards natural elements and away from negative emotions, leading to a reduction in stress. Despite the known negative associations between urban living and health outcomes [ 25 , 26 ], recent studies have shown that exposure to certain urban environments can be beneficial for well-being [ 27 , 28 ]. Historic and cultural environments especially have emerged as offering the most restorative potential of urban environments [ 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], although the restorative effect of historic settings seems to be smaller than that of natural environments [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This protective effect might be also disease-specific as social-environmental activation plays a major role in specific psychiatric diseases, such as depression. Suicidality and self-harm (as other major psychiatric clinical features) are higher in cities than in the countryside in the United Kingdom and Ireland ( 17 ).…”
Section: Discussionmentioning
confidence: 99%